University Entrepreneurial Ecosystems and Graduate Entrepreneurship - Edgardo Ayala-Gaytan; Elvira E
This article addresses the measurable outcomes of a university-based entrepreneurial ecosystem in an emerging economy beyond entrepreneurial intention, patents or academic spin-offs. A logit model with fixed effects by decades was applied to data from over 17,000 alumni who graduated between 1943 and 2017 to identify the existence of a structural change in the rates of entrepreneurship before graduation and up to five years after graduation. This structural change was related to each stage in the evolution of the university entrepreneurial ecosystem. Findings show that as the ecosystem elements were introduced, the probability of founding a business before graduation increased with each decade. Additionally, results suggest that the strategies to redefine and expand academic functions, adapt organizational structures and diversify the university$1 (Bs curriculum supported a significant increase in the entrepreneurship rate of alumni. This evidence contributes to our understanding of the impact of strategic decisions to drive entrepreneurship from intention to action.s